Professor Mahmoud Shojaei (1925–2018), Memorial letter - Karimi, Javad (Journal of insect biodiversity and systematics, 2021)
Prof. Mahmoud Shojaei, a prestigious professor of entomology at Tehran University and Islamic Azad University, passed away at 93 on November 25, 2018. Prof. Shojaei's contribution to entomology was profound and enduring, 63 years of teaching and research. He was former Dean of Faculty of Agriculture, University of Tehran and manager of Jalal Afshar's Zoological Museum, at Karaj campus of the University of Tehran.